Nanog Reverses the Effects of Organismal Aging on Mesenchymal Stem Cell Proliferation and Myogenic Differentiation Potential123. (27th November 2012) - Han, Juhee; Mistriotis, Panagiotis; Lei, Pedro; Wang, Dan; Liu, Song; Andreadis, Stelios T.
Abstract: Although the therapeutic potential of mesenchymal stem cells (MSCs) is widely accepted, loss of cell function due to donor aging or culture senescence are major limiting factors hampering their clinical application. Our laboratory recently showed that MSCs originating from older donors suffer from limited proliferative capacity and significantly reduced myogenic differentiation potential. This is a major concern, as the patients most likely to suffer from cardiovascular disease are elderly. Here we tested the hypothesis that a single pluripotency‐associated transcription factor, namely Nanog, may reverse the proliferation and differentiation potential of bone marrow‐derived MSC (BM‐MSC) from adult donors. Microarray analysis showed that adult (a)BM‐MSC expressing Nanog clustered close to Nanog‐expressing neonatal cells. Nanog markedly upregulated genes involved in cell cycle, DNA replication, and DNA damage repair and enhanced the proliferation rate and clonogenic capacity of aBM‐MSC. Notably, Nanog reversed the myogenic differentiation potential and restored the contractile function of aBM‐MSC to a similar level as that of neonatal (n)BM‐MSC. The effect of Nanog on contractility was mediated—at least in part—through activation of the TGF‐β pathway by diffusible factors secreted in the conditioned medium of Nanog‐expressing BM‐MSC. Overall, our results suggest that Nanog may be used to overcome the effects of organismal aging on aBM‐MSC, thereby increasing the potential of MSC from aged donors for cellular therapy and tissue regeneration. STEM CELLS 2012;30:2746–2759